Development of Potato Chips (Alou) with Northern Thai Green Chili Paste (Nam Phrik Noom) Flavor - Osiriphun, Sukhuntha; Wongsuriyasak, Somchai; Chakrabhandhu, Yasinee (Food and Applied Bioscience Journal, 2018)
The aim of this research was to develop the product of potato chips with northern Thai styled green chili paste flavor which is acceptable for adolescents and adults. This product consists of 91.8% potato chips and 8.2% green chili powder. Proximate analysis of fresh potato, dried potato, and fried potato chip samples was carried out. Prototypes of green chili paste were developed by comparing with two well-known brands in Chiang Mai province, and the most suitable formulation was used for developing the product. The processes of preparing green chili powder of two well-known brands in Chiang Mai province were the same as that for the prototype, with a heating time at 60°C of 12 h. As far as the sensory analysis results are concerned, the mean scores for overall liking and consumer acceptability of the prototypes were 5.8±1.4% and 95%, respectively. As for the physical qualities of the product, it was found that lightness was 53.86±0.01, redness was 0.28±0.03, yellowness was 24.91±0.59, and water activity was 0.35. The results indicate that the optimum formula consisted of fresh green chili, garlic, shallot, and fish sauce at 75%, 10%, 10%, and 5%, respectively.